2019
DOI: 10.11648/j.wjfst.20190301.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of Acute Toxicity and the Effect of the Aqueous Extract of a Formulation of Three Edibles Mushrooms on Oxidative Stress Induced in Rats

Abstract: Edible mushrooms, especially Pleurotus spp. contain a wide variety of biomolecules that can play a protective role against oxidative damage. We investigate the effect of formulation of the aqueous extract of three edibles mushrooms commonly consumed in Cameroon on oxidative stress induced in rats induced by lead acetate: Pleurotus pulmonarius, Pleurotus floridanus and Pleurotus sajor-caju. The formulation made of the three species (1w:1w:1w) were dissolved in distilled water for acute toxicity (at 2000 mg/kg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Cameroon, the works of Etoundi et al, showed that Pleurotus mushrooms had; significant hypoglycaemic activity in the treatment of diabetes induced in rats, and protective effects against lead-induced hepato-renal damage in rats were also demonstrated [7] [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, the works of Etoundi et al, showed that Pleurotus mushrooms had; significant hypoglycaemic activity in the treatment of diabetes induced in rats, and protective effects against lead-induced hepato-renal damage in rats were also demonstrated [7] [8] .…”
Section: Introductionmentioning
confidence: 99%